1993
DOI: 10.1073/pnas.90.17.8093
|View full text |Cite
|
Sign up to set email alerts
|

Probing the function of Drosophila melanogaster accessory glands by directed cell ablation.

Abstract: The female Drosophila melanogaster fly undergoes behavioral changes after mating, including an increase in egg laying and an avoidance of remating. Accessory-gland products elicit these changes transiently when introduced into unmated female flies. We report here the generation and phenotype of flies that lack functional accessory-gland main cells as a consequence of genetically directed delivery of diphtheria toxin subunit A to those ceUls. Only main-cell secretions are essential for the short-term inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
227
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(241 citation statements)
references
References 30 publications
(33 reference statements)
8
227
0
Order By: Relevance
“…Nor did egg density contribute to daughter fitness because we statistically accounted for vial egg density in all of our analyses of daughter traits. Also, though exposure to Acps increases egg production in virgin females (Kalb et al 1993), we found that additional exposure to Acps did not influence egg production in inseminated females.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Nor did egg density contribute to daughter fitness because we statistically accounted for vial egg density in all of our analyses of daughter traits. Also, though exposure to Acps increases egg production in virgin females (Kalb et al 1993), we found that additional exposure to Acps did not influence egg production in inseminated females.…”
Section: Discussionmentioning
confidence: 68%
“…At maternal age day 2, we exposed each female to three fresh virgin Dahomey males for four hours. At maternal age day 4, we randomly assigned the females to one of the three additional mating treatments: no additional mating, additional mating with five fresh males that were sterile and lacked production of main-cell Acps (DTA-E males; Kalb et al 1993), or additional mating with five fresh males that were sterile but produced main-cell Acps (sons of tudor females; Boswell & Mahowald 1985). All of the females were provided with fresh vials and the additional mating treatment females were provided with fresh males every 2 days from maternal age days 4 to 10.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, D. melanogaster males transfer many more sperm than females are capable of storing (Gilbert 1981) and egg laying is known to be in£uenced by seminal proteins rather than by variation in sperm supply (e.g. Chen et al 1988;Kalb et al 1993;Herndon & Wolfner 1995). It is also unlikely that this divergence is the result of di¡erential larval survival brought about through sperm length di¡erences.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, male o¡spring of tudor females fail to produce germline cells, and are likewise spermless but produce normal seminal £uid (SchÏpbach & Wieschaus 1986). The results using these males were compared with the results of remating with sterile DTA (which bear a diphtheria toxin transgene) males, which lack an accessory gland and thus produce no seminal £uid proteins (Kalb et al 1993). A third-chromosome extracted line (B3^09) from Beltsville, was used as a control with normal fertility.…”
Section: Methodsmentioning
confidence: 99%